Pengetahuan dan perilaku mahasiswa keperawatan vokasi dalam upaya preventif di masa pandemi Covid-19 - Praty Milindasari; Juniah Juniah (Holistik Jurnal Kesehatan, 2022)
Background: At the end of 2019 the world was attacked by the disease Covid-19 (Corona Virus Disease-19) or the Coronavirus. The number of cases and deaths due to the Covid-19 outbreak continues to occur in various countries in the world with new cases being reported every day. Preventive efforts carried out by vocational nursing students and information about Covid-19 help themselves to prevent and overcome Covid-19 problems.Purpose: Knowing the relationship between knowledge and behavior of vocational nursing students in preventive efforts during the Covid-19 pandemicMethod: Quantitative research with a correlation design approach with a population was D3 nursing students at three nursing education institutions in the Bandar Lampung City area, and data collection was carried out in October 2021. The sample size was 90 respondents. The sampling technique was taken using the Simple random sampling technique, which is the simplest probability sampling technique. The instrument was used as a questionnaire to determine the knowledge and behavior of students about preventive efforts during the Covid-19 pandemic.Results: From the research, it is known that 88.9% of students have good knowledge. 82 students (91.1%), students who use hand sanitizers 84 (93.3%), students who keep their distance 68 (75.6%), students who have the habit of touching their eyes, nose, and mouth 46 (51.1 %), and students who experienced an increase in endurance were 76 (84.4%).Conclusion: There is a significant relationship between knowledge and efforts to prevent the use of masks, use of hand sanitizers, maintain distance, and increase endurance (p-value < 0.05), and there is no significant relationship between knowledge and behavior of touching eyes, nose, and mouth (p-value > 0.05).Suggestion: Expand knowledge related to Covid-19 by following developments and continuing to take preventive actions or efforts in daily life to prevent further Covid-19 transmission.Keywords: Knowledge; Behavior; Student of Nursing; Prevention; Covid-19 Pendahuluan: Penghujung tahun 2019 dunia diserang oleh penyakit Covid-19 (Corona Virus Desease-19) atau virus Corona. Jumlah kasus dan korban jiwa akibat wabah Covid-19 ini terus terjadi di berbagai negara di dunia dengan terus dilaporkannya kasus baru setiap harinya. Upaya preventif yang dilakukan oleh mahasiswa keperawatan vokasional dan informasi tentang Covid-19 membantu diri mereka untuk mencegah dan mengatasi masalah Covid-19.Tujuan: Mengetahui hubungan pengetahuan dan perilaku mahasiswa keperawatan dalam upaya preventif di masa pandemi Covid-19Metode: Penelitian kuantitatif dengan pendekatan correlation designs, populasinya mahasiswa Keperawatan swasta jenjang D3 keperawatan di tiga institusi pendidikan perawat  di wilayah Kota Bandar Lampung, dan pengambilan data dilaksanakan pada bulan Oktober 2021. Besarnya sampel pada sebanyak 90 responden. Teknik sampling yang diambil menggunakan teknik Simple random sampling, yang merupakan teknik probabilitas sampling paling sederhana. Instrumen yang digunakan berupa kuesioner untuk mengetahui pengetahuan dan prilaku mahasiswa tentang upaya preventif  di masa pandemik Covid-19Hasil: Dari penelitian didapatkan mahasiswa yang memiliki pengetahuan baik sebanyak 88,9%. mahasiswa yang memakai masker sebanyak 82 (91,1%), mahasiswa yang menggunakan hand sanitizer 84 (93,3%), mahasiswa yang menjaga jarak 68 (75,6%), mahasiswa yang mempunyai kebiasaan menyentuh mata, hidung, dan mulut sebanyak 46 (51,1%), dan mahasiswa yang meningkatkan daya tahan tubuh sebanyak 76 (84,4%).Simpulan: Terdapat hubungan yang signifikan antara pengetahuan dengan upaya preventif memakai masker, menggunakan hand sanitizer, menjaga jarak, dan meningkatkan daya tahan tubuh (p-value < 0,05), dan tidak terdapat hubungan yang signifikan antara pengetahuan dengan perilaku menyentuh mata, hidung, dan mulut (p-value > 0,05).Saran: Perluas pengetahuan terkait dengan Covid-19 dengan mengikuti perkembangan yang terjadi dan lakukan terus tindakan atau upaya preventif dalam kehidupan sehari-hari untuk mencegah penularan lebih lanjut Covid-19.